english: english - Habibie, Rudy; Arida Mahmudyah (Unram Law Review, 2023)
The existence of fictitious credit cases indicates that banks need to provide more supervision in lending, and the prudential principle of banking needs to be correctly implemented. The purpose of this article is to find out the bank's responsibility to customers whose identities are used without permission in fictitious loans in terms of the Civil Code. The normative method is used in this article. The type of approach used is the statutory approach and the case approach. The legal material collection technique used is a literature study from books, laws and regulations, papers, and journals that relate to the issues discussed. The results of the discussion show that in the provisions of Articles 1365 and 1367 of the Civil Code, the employees of the bank or the bank concerned are required to provide accountability in the form of compensation to bank customers whose identities are used without permission in fictitious credit, in the provisions of Article 1365 of the Civil Code it does not further regulate the amount to be replaced in an unlawful act.